Effectiveness of transradial access in percutaneous coronary interventionism. - Javier Almeida Gómez; Abel Yoandri Leyva Quert; Emil Andrés Moronta Soriano; Joel Brooks Tamayo; Tomás C. Méndez Peralta; Manuel Valdés Recarey (ECIMED, 2011)
Introduction Transradial approach for coronary interventional procedures is becoming moreattractive mainly for shortening hospitalization and dramatically reduces access-site complications. At present, the transradial approach has become theprimary vascular access for revascularization at the Hermanos Ameijeiras´scatheterization laboratory.Objective To determine the effectiveness of the transradial approach and the short termsurvival free of major cardiac eventsMethod An observational prospective study was done in 279 patients who underwentpercutaneous coronary interventions from September 2009 to May 2010. Themajor cardiac events included were death, non fatal myocardial infarction, urgentvessel revascularization and major bleeding. The survival rates were estimatedby the Kaplan Meier method and compared by means of the Log Ranktest.Results Radial access was used in 68, 46 % cases and the success rate was similar tothe transfemoral approach (93.2% vs. 89.8%, p=0.325), there was no differenceregarding the treated lesions, deployed stents, procedure and fluoroscopytimes. There were less major cardiac events when the TRA was used (2.1% vs6.8%, p=0.049). The numbers of patients free from major cardiac events at 30days were 97.9% and 93.18% for radial and femoral approaches respectively.Conclusions In summary, the TRA is safe and effective during PCI with short term survivalfree of major cardiac events that has surpassed the transfemoral approach.